2012
DOI: 10.4103/0972-124x.106911
|View full text |Cite
|
Sign up to set email alerts
|

Influence of moderate to severe chronic periodontitis on dental pulp

Abstract: Background:The relationship between periodontal disease and dental pulp changes is controversial and has been debated for many years. This human study was performed to evaluate the possible effects of moderate to advanced periodontal disease on the different aspect of dental pulp structure.Materials and Methods:Twenty hopeless permanent teeth were extracted from systemically healthy adults because of moderate to advanced chronic periodontitis, with a bone loss of >6 mm and a mobility of grade 2 or 3. Upon extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 18 publications
(32 reference statements)
3
11
0
Order By: Relevance
“…We found that teeth with severe periodontitis with a hopeless clinical prognosis could result in fibrosis, apical inflammation and internal/external resorption but did not lead to pulpal necrosis. This study was a case-control investigation and reaffirmed the previous studies’ findings that inflammation and degenerative pulpal alterations such as fibrosis are the most frequent impact of periodontal disease on pulpal tissue ( 5 , 22 , 23 ). However, the previous studies utilised cross-sectional histological sections, whereas this study used longitudinal histological sections.…”
Section: Discussionsupporting
confidence: 88%
“…We found that teeth with severe periodontitis with a hopeless clinical prognosis could result in fibrosis, apical inflammation and internal/external resorption but did not lead to pulpal necrosis. This study was a case-control investigation and reaffirmed the previous studies’ findings that inflammation and degenerative pulpal alterations such as fibrosis are the most frequent impact of periodontal disease on pulpal tissue ( 5 , 22 , 23 ). However, the previous studies utilised cross-sectional histological sections, whereas this study used longitudinal histological sections.…”
Section: Discussionsupporting
confidence: 88%
“…In our study, 46.8% of patients and 8.1% of teeth had pulp stones, and pulp stones were most common in group 4 (79.2%) and the least common in group 1 (20.8%). Our results support the hypothesis that pulp degeneration is associated with periodontal disease (2,18,19). The variance between the studies can be ascribed to differences in populations, radiography methods, evaluated teeth, and the experience of the examiner.…”
Section: Discussionsupporting
confidence: 80%
“…The most common pulpal changes reported in literature are inflammatory and degenerative changes in the form of fibrosis and calcifications and the results of our study are in agreement with earlier studies. [ 7 12 13 ] These studies, however, employed cross-sectional specimens whereas we employed longitudinal sections. Although the chances of developing an artifact are more in longitudinal section, it allows to view the pulp entirely and also its relations to accessory and lateral canals.…”
Section: Discussionmentioning
confidence: 99%